Teknik Friendly Match Man to Man untuk Menyelesaikan Operasi Hitung Penjumlahan dan Pengurangan Bilangan Bulat - Shofaul Hikmah (Balai Diklat Keagamaan Semarang, 2020)
The Man to Man Friendly Match Technique is a new breakthrough created to help Madrasah Ibtidaiyah students complete the operation of adding and subtracting integers. This technique emerged as a result of the writer's concern as one of the subjects of Mathematics in Madrasah Ibtidaiyah who saw the low interest and learning outcomes of students in the material operations of calculating the addition and subtraction of integers. Man to Man Friendly Match Technique is a technique that combines the game as an activity that is very closely related to the daily lives of students with the concept of arithmetic operations of addition and subtraction of integers